Lessons Learned From a Boston Community Health Center Promoting the Human Papilloma Virus Vaccine in a Minority Adult Population - Hope A. Ricciotti MD; Sasha Girouard BA; Gail Pokorney BA; Laura E. Dodge MPH; Michele R. Hacker ScD, MSPH (SAGE Publishing, 2010)
This quality improvement study aims to examine knowledge and attitudes about human papillomavirus (HPV) vaccination among women ages 18 through 26 in a Boston community health center to increase uptake of the HPV vaccine in the local community. This cross-sectional study was conducted from August 2007 to July 2008 at an urban community health center in Roxbury, Massachusetts. Women offered HPV vaccines were asked to complete a questionnaire. Eighty-four percent of participants had heard of the HPV vaccine. A higher percentage (69%) of minority women in this study as compared with those in other studies knew the vaccine protects against cervical cancer. Forty-two percent of women came to their appointment for the purpose of being vaccinated. The remaining 58% came for another reason and received vaccination upon health care provider recommendation. Only 38% of participants reported perceived risk for HPV infection as a motivation for vaccination. These findings suggest that generalizations of attitudes and knowledge about the HPV vaccine should not be made with regard to race and ethnicity alone, but rather need to be based on surveys of the specific local population served. In addition, education about HPV risk should be continued, especially about risk factors for HPV infection.